The Service Program Design as A Model for Preparing Future Teachers’ Interpersonal Skills: A Descriptive Study - Yulina, Christina Atika; Prasodjo, Bernadetha Ambarsari (JUPE : Jurnal Pendidikan Mandala, 2025)
The focus of this descriptive study is to depict the implementation of the Service Program Design (SPD) course offered by the English Language Education Study Program (ELESP) in a university in Yogyakarta. The study focuses on describing the course structure, objectives, weekly meetings, and highlighted activities conducted throughout the semester. Lesson plans, assignments, students’ reflections, and interviews with lecturers and eight chosen students (picked based on questionnaire findings from a prior study) were among the methods used to gather data. Through a service-oriented framework that prioritizes creativity, collaboration, and reflection, the Service Program Design course was established to foster professional development.  While this paper focuses on describing the implementation of the course, findings from a related study with alumni have indicated that the SPD course indeed contributed to the development of specific interpersonal skills among graduates.